American pie : the anatomy of vulgar teen comedy - Osgerby, Bill (London ; New York : Routledge, 2020)
"American Pie (1999) is a film that exemplifies that most disparaged of movie genres - the vulgar teen comedy. Largely aimed at young audiences, the vulgar teen comedy is characterised by a brazenly over-the-top humour rooted in the salacious, the scatological and the squirmingly tasteless. American Pie represents the most commercially successful example of the vulgar teen comedy, and this book analyses the film's development, audience-appeal and cultural significance. Particular consideration is given to the relationship between American Pie's success and broad shifts within both the youth market and the film business. Attention is also given to American Pie's representations of youth, gender and sexuality; together with the distinctive character of the film's comedy and the enduring place of such humour in contemporary popular culture. While chiefly focusing on the original American Pie movie, the book also considers the development of the American Pie film franchise as a whole, with discussion of the movie's three sequels and four direct-to-DVD releases. The book also charts the history, nature and appeal of vulgar teen comedy as a whole, providing the first concerted analysis of this generally overlooked category of youth film"--
Serving up American pie : youth, cinema and vulgar teen comedy -- A recipe for success : the rise of American pie -- Getting a gross from gross-out : Hollywood, the youth market and American pie -- 'Like warm apple pie ...' : gross-out humour and the vulgar teen comedy -- 'High school was awesome' : constructions of youth in American pie -- Vulgar teen comedy : the last crumbs.
OCLC-licensed vendor bibliographic record.
Keywords: American pie (Motion picture); Teenagers in motion pictures; Vulgarity in motion pictures; Teen films -- United States -- History and criticism; Comedy films -- United States -- History and criticism; SOCIAL SCIENCE / Media Studies